Termination simpliciter, a dismissal without just cause and excuse? an analysis of Omar bin Othman v Kulim Advanced Technologies Sdn Bhd (previously known as KTPC Technologies Sdn Bhd)[2019] 1 MLJ 625 (CA) - Ali Mohamed, Ashgar Ali; Sardar Baig, Farheen Baig; Eishan Jan, Mohammad Naqib; Ahmad, Muhamad Hassan (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
This article addresses on the requirements of establishing just cause or excuse before terminating the employment relationship. In relation to the above, the recent Court of Appeal’s decision in Omar bin Othman v Kulim Advanced Technologies Sdn Bhd (previously known as KTPC Technologies Sdn Bhd), is discussed where the High Court held inter alia, that termination by mutual consent of the parties is not termination simpliciter, and that the acceptance of the payment in lieu of notice with no objection ends lawfully the employment relationship.